Pengaruh Belanja Daerah Sektor Kesehatan dan Belanja Daerah Sektor Pendidikan terhadap Indeks Pembangunan Manusia di Provinsi Kalimantan Selatan - Kevin Chandra (PPJP Universitas Lambung Mangkurat, 2022)
The objectives of this research are (1) To find out whether Health Sector Expenditures and Education Sector Expenditures are Persistently Influential on Human Development Index in South Kalimantan Province for the period 2010-2019; (2) To find out whether Health Sector Expenditure and Education Sector Expenditure Simultaneously Influence Human Development Index in South Kalimantan Province for the period 2010-2019; (3) To find out what variables are dominantly affecting Human Development Index in South Kalimantan Province 2010-2019. This research is expected to understand local governments, private groups, and community agencies' interest in economic development in South Kalimantan Province. This research method uses data collection methods by obtaining data from central statistical agencies and related agencies. After that, regression analysis is performed to see the influence of the independent variables on the dependent. The software used for regression analysis is Eviews. The results of this study indicate that regional spending on the health sector has a significant effect and a positive direction on the index of human development, and regional expenditure on the education sector has a significant effect and positive direction on the index of human development